“It’s really tricky to open a can of worms where you have nothing to offer" : an interpretative phenomenological analysis of health professionals' perspective on the potential introduction of the ACEs screen to a paediatric department in New Zealand, using an Implementation Science approach : a thesis presented in partial fulfilment of the requirement for the degree of Master of Science endorsed in Health Psychology at Massey University, Albany, New Zealand - De Silva, Kavindri Kinkini Saranguhewa (Massey University, 2023)
The current study aimed to examine how to introduce Adverse Childhood Experiences (ACEs) screening into a Paediatric setting in New Zealand (NZ). At present there are significant health inequities within the NZ population. Research has indicated that an underlying and often unaddressed issue contributing to the development of health inequity is the accumulation of childhood adversities. This phenomenon was named ACEs. ACEs was also found to be a leading cause of early death in adults. The discovery of this public health issue prompted those in the field to identify ACEs early. However, it is yet to be implemented in NZ health settings. Therefore, the current study examines health professionals' perspectives on introducing the ACEs questionnaire into routine practice in a Paediatric Department in NZ. This study used knowledge from Implementation Science (IS) method to identify the most effective way to implement this questionnaire in the hospital setting. The Replicating Effective Program (REPs) Framework was identified as the best IS framework for this project. The focus of this project was on the first stage of the REP framework, the pre-condition stage, particularly identifying the barriers that could impede on the implementation process and the facilitators that can assist in enhancing screening practices. Interpretative Phenomenological Analysis (IPA) was the methodology and analysis utilised for this project. Purposeful selection was carried out and five participants were recruited and interviewed for the project: three Paediatricians and two Allied health workers. Four superordinate themes emerged from the analysis. They are Knowledge, training, and perspective on ACEs; Reflecting on current practices; Questions, concerns, and other barriers; and Suggested improvements. Further subordinate themes also emerged under three of the four superordinate themes. These findings from the study have provided deeper perspectives into barriers that inhibit health professionals from screening for ACEs in daily practices. The findings have also revealed the facilitators that can promote ACEs screening within the Paediatric Department. These findings has the opportunity to begin the process of ACEs screening in a Paediatric setting in NZ and begin the process of identifying ACEs in an effort to reduce health inequity in the NZ population.
Keywords: 520304 Health psychology